ANALISA DAMPAK HUKUM RENCANA DIKELUARKANNYA BIDANG USAHA PENYELENGGARAAN PELAYANAN NAVIGASI PENERBANGAN DARI DAFTAR NEGATIF INVESTASI (DNI) (Lex Jurnalica, 2020)
AbstractThe government of Indonesia plans to relax the Presidential Regulation (Perpres) No. 44 of 2016 concerning the List of Closed Business Sectors and Opened Business Sectors with Investment Requirements. In the latest Perpres which is planned to be issued in 2020 the government plans to issue 14 of the 20 list of negative investments contained in Perpres No. 44 of 2016, one of which is in the business of providing Aviation Navigation Services. The Organization of Aviation Navigation Services which was previously a closed business field for Investment will now become an open business field that can be entered into Domestic and Foreign Capital. With the opening of the closed business field into an open business field, it certainly has legal consequences for the Prepres that is planned to be issued and also other impacts such as changes in the legal entity of the Indonesian Air Navigation Service Provider. Keywords: Negative List of Investments (DNI), Air Navigation Service Providers, Investment.AbstrakPemerintah berencana melakukan relaksasi terhadap Peraturan Presiden (Perpres) No 44 Tahun 2016 Tentang Daftar Bidang Usaha yang Tertutup dan Bidang Usaha Yang Terbuka dengan Persyaratan Penanaman Modal. Dalam Perpres terbaru yang rencananya akan dikeluarkan di Tahun 2020 ini pemerintah berencana mengeluarkan 14 dari 20 Daftar investasi negatif yang termuat dalam perpres No 44 Tahun 2016 salah satunya dalam bidang usaha Penyelenggaraan Pelayanan Navigasi Penerbangan. Penyelenggaraan Pelayanan Navigasi Penerbangan yang sebelumnya menjadi bidang usaha yang tertutup bagi Penanaman Modal kini akan menjadi bidang usaha terbuka yang dapat dimasuki Modal Dalam Negeri maupun Modal Asing. Dengan dibukanya bidang usaha tertutup tersebut menjadi bidang usaha terbuka tentunya memiliki konsekuensi Hukum terhadap Prepres yang rencananya dikeluarkan tersebut dan juga dampak dampak lain seperti berubahnya badan hukum usaha Penyelenggara Navigasi Penerbangan Indonesia.     Kata Kunci : Daftar Negatif Investai (DNI), Penyelenggaraan Pelayanan Navigasi Penerbangan, Penanaman Modal.